Analisis Implementasi Etika Bisnis Islam dalam Bisnis Penginapan Syariah di Kota Sungai Penuh - Kartika, Vhyola Dewi; Sarmigi, Elex; Sumanti, Eva (Institut Agama Islam Negeri Parepare, 2025)
Sharia-based accommodations have been growing in response to the increasing awareness among Muslim communities about the importance of services that align with Islamic principles. This study aims to analyze the implementation of Islamic business ethics in Sharia accommodation businesses in Sungai Penuh City, focusing on management, services, facilities, and compliance with Sharia regulations. Using a qualitative case study approach, data were collected through interviews with managers, direct observation, and document analysis. The findings show that Sharia principles are applied through policies on non-mahram interactions, the availability of prayer facilities, the use of Sharia-compliant financial systems, and halal standards in food and beverages. However, challenges remain, including limited public understanding and the lack of specific regulations governing Sharia accommodations. This study is expected to offer insights for hospitality businesses in improving Sharia-based services and serve as a reference for government policy development.